'If the results are negative, they motivate us'. Experiences of early infant diagnosis of HIV and engagement in Option B+. Issue 2 (1st February 2021) - Etoori, David; Renju, Jenny; Reniers, Georges; Ndhlovu, Violet; Ndubane, Sherly; Makhubela, Princess; Maritze, Meriam; Gomez-Olive, Francesc Xavier; Wringe, Alison
ABSTRACT: Few studies have explored the relationship between early infant diagnosis (EID) of HIV and mothers' engagement in care under Option B+. We conducted in-depth interviews with 20 women who initiated antiretroviral therapy (ART) under Option B+ in rural South Africa to explore the interactions between EID and maternal care engagement. Drawing on practice theory, we identified themes relating to Option B+ care engagement and EID. Women's practice of engagement with HIV care shaped their decision-making around EID. Mothers who disengaged from care during pregnancy were less inclined to utilise EID as they lacked information about its availability and benefits. For some mothers, tensions between wanting to breastfeed and perceptions that it could facilitate transmission led to repeated utilisation of EID as reassurance that the child remained negative. Some mothers used their child's negative result as a proxy for their status, subsequently disengaging from care. For some participants, an HIV diagnosis of their infant and the subsequent double burden of treatment visits for themselves and their infant, contributed to their disengagement. Women's care-seeking practices for themselves and their infants work in a symbiotic ecosystem and should be viewed interdependently to tailor interventions to improve EID uptake and Option B+ care engagement.